Pengembangan E-Commerce Berbasis Web Pada Dyzan Store Wonogiri - Setiawan, Dicky Agus; Susanto, Rudi; Wijiyanto, Wijiyanto (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2021)
DYZan Store is one of the online shops in Wonogiri Regency which is engaged in fashion by selling various community needs ranging from children's fashion to adults, especially women. DYZan Store provides information updates to resellers using Whatsapp media so that there is often a lack of updated stock information. In addition, not a few resellers also complain because of the accumulation of photo data which causes swelling of the internal memory. This is because DYZan Store always sends pictures to the reseller group. The system development method used in this research is the waterfall method, then analysis of system weaknesses uses PIECES, while the data modeling method uses UML (Unified Modeling Language). The programming language used is PHP MYSQL with the laravel framework. System testing using black box testing. The results show that the website has passed the error test and is functioning as expected. The development of the DYZan Store e-commerce has the potential to make it easier for resellers to carry out transaction activities and make it easier for DYZan Store owners to process products and reports.